ISLAMIC BANKING AND ECONOMIC GROWTH: APPLYING THE CONVENTIONAL HYPOTHESIS - Ahmad Jawad; Klein Christian (Journal of Islamic Monetary Economics and Finance, 2019)
Growth in Islamic banking has gained lot of interest and attention during last few years. The debate currently shifts from theoretical to empirical framework. The growth in empirical work has given rise to a new concept, which can be called as “Islamic banking development” (IBD). It will be interesting to test nexus between IBD and growth, since literature suggests a positive result for conventional finance and growth. Our study uses a panel of 24 countries for a period of 11 years using annual data (2004-2014) to test conventional hypothesis of supply leading or demand following between IBD and growth. In addition, we also investigate direction of causality in a panel setting between the two. Apart from the topic, this paper differs from existing limited literature, on the basis of dataset used and the estimation procedure to assess the nexus. Our results suggest that IBD affect growth positively. Comprehensive tests suggest the presence of a long run relationship between IBD and growth. Moreover, the direction of causality seems to follow supply leading hypothesis: IBD affects economic growth, and that evidence on a reverse causality was not found. This is true, even when we control for CFD.